The Nation State, Globalization, and the Modern Institution of the University - Kwiek, Marek (New York-Oxford: Berghahn Books, 2000)
The question of the decline of the nation-state is parallel, in my account, to questions about the human and social consequences of globalisation, the decline of modernity, the end of history, the ‘death of the intellectual’ and the decline of the modern institution of the university. These questions form an aggregate of problems with which modern thought seems unable to cope. New cultural, social, political and economic surroundings brought about by globalisation seem to require a totally new language.
Keywords: University; Welfare state; nation-state; Globalization